2018
DOI: 10.1088/1361-6528/aaebd6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of contact area and electron transport across platinum nanocontacts for scanning probe microscopy and electrical nanodevices

Abstract: Conductive modes of atomic force microscopy are widely used to characterize the electronic properties of materials, and in such measurements, contact size is typically determined from current flow. Conversely, in nanodevice applications, the current flow is predicted from the estimated contact size. In both cases, it is very common to relate the contact size and current flow using well-established ballistic electron transport theory. Here we performed 19 electromechanical tests of platinum nanocontacts with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Separate in situ TEM adhesion experiments demonstrated the critical role that surface chemistry plays in the deformation of platinum nanocontacts. Liquid-like diffusive behavior is not observed in selfmated platinum nanocontacts, 85 likely due to the presence of surface monolayers of oxygen or carbonaceous material (Figure 6c-d), 86 which is consistent with atomistic simulations. 87 These surface layers prevent the motion of the surface steps that are required for diffusive plasticity.…”
Section: Surface Adhesion (Or Cold-welding) Of Metal Contactssupporting
confidence: 78%
See 2 more Smart Citations
“…Separate in situ TEM adhesion experiments demonstrated the critical role that surface chemistry plays in the deformation of platinum nanocontacts. Liquid-like diffusive behavior is not observed in selfmated platinum nanocontacts, 85 likely due to the presence of surface monolayers of oxygen or carbonaceous material (Figure 6c-d), 86 which is consistent with atomistic simulations. 87 These surface layers prevent the motion of the surface steps that are required for diffusive plasticity.…”
Section: Surface Adhesion (Or Cold-welding) Of Metal Contactssupporting
confidence: 78%
“…(The scale bars are 5 nm in length.) However, subsurface defect-based plasticity is observed85 in platinum nanocontacts (c), and real-time electrical measurements86 are consistent with the presence of atomic-scale surface layers (d), which may disrupt surface diffusion. (a, b) were reproduced with permission from Reference 80, © 2014 Nature Publishing Group.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Contact tests were performed inside of a transmission electron microscope (2100F, JEOL, Tokyo, Japan) operated at 200 keV with the use of an in situ nanoindenter (PI-95 Picoindenter, Hysitron Inc., Minneapolis, MN). The experimental setup is similar to that of [37][38][39] and is shown in Fig. 1(a,b).…”
Section: In Situ Tem Experimental Measurementsmentioning
confidence: 99%
“…15 Several CAFM investigations have focused on the relationship between current transfer and contact area, both of which should increase with pressure. 7,[16][17][18][19] However, some of these studies showed that, for very small contacts ($50 nm or less), the expected current-contact area relationship does not always hold true. 16,17,20,21 One explanation for this lack of correlation is that trace contamination of the contact can inhibit conduction 22 such that the magnitude of the electrical current does not reect the size of the contact.…”
Section: Introductionmentioning
confidence: 99%